2016
DOI: 10.1111/tbed.12524
|View full text |Cite
|
Sign up to set email alerts
|

Serological Study of Exposure to Selected Arthropod-Borne Pathogens in European Bison (Bison bonasus) in Poland

Abstract: Bison bonasus is an indigenous species of Central and Eastern Europe with the largest wild population inhabiting Białowieża Primeval Forest; however, free-living and captive European bison are reared in many countries around the world. Despite that the European bison was rescued from the extinction after the First World War, it remains as endangered species. Changing environment as well as human activity may have contributed to the observed increase of the risk of the emergence and re-emergence of pathogens. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…During the epizootics more than 30% of European bison kept in Hardehausen died, and the surviving animals received a vaccine containing homologous inactivated BTV-8 [69]. BTV-8 epizootics did not reach Poland; however another strain, BTV-14, was detected almost simultaneously in cattle and in European bison at the northeast of Poland, near the Belarusian and Lithuanian borders [11,70].…”
Section: Emerging Re-emerging and Vector-borne Pathogens Infecting mentioning
confidence: 99%
See 4 more Smart Citations
“…During the epizootics more than 30% of European bison kept in Hardehausen died, and the surviving animals received a vaccine containing homologous inactivated BTV-8 [69]. BTV-8 epizootics did not reach Poland; however another strain, BTV-14, was detected almost simultaneously in cattle and in European bison at the northeast of Poland, near the Belarusian and Lithuanian borders [11,70].…”
Section: Emerging Re-emerging and Vector-borne Pathogens Infecting mentioning
confidence: 99%
“…Therefore, combining this with the dynamics of geographical spread of BTV-14 in Poland, use of some illegal vaccine containing or contaminated with this BTV strain was suggested [71]. Serosurveillance of BTV in European bison showed that the infections occurred only in the eastern populations [11]. Interestingly, despite that the discovered BTV-14 has been described as attenuated strain causing only subclinical infection in cattle, significant association between health status of European bison and the presence of specific antibodies was observed [11].…”
Section: Emerging Re-emerging and Vector-borne Pathogens Infecting mentioning
confidence: 99%
See 3 more Smart Citations